Association between the side effect induced by COVID-19 vaccines and the immune regulatory gene polymorphism - Chen, Ding-Ping; Wen, Ying-Hao; Lin, Wei-Tzu; Hsu, Fang-Ping (Frontiers in Immunology, 2022)
People often worry about the side effects after vaccination, reducing the willingness to vaccinate. Thus, we tried to find out the risk of single nucleotide polymorphism (SNP) vaccines to improve the willingness and confidence in vaccination. Allergic and inflammatory reactions are the common vaccine side effects caused by immune system overreaction. In addition, a previous study showed significantly higher frequency of febrile reactions to measles vaccines in American Indians than in Caucasian children, indicating that the side effects varied in accordance with genetic polymorphisms in individuals. Thus, SNPs of immune regulatory genes, cytotoxic T-lymphocyte-associated protein 4 (CTLA4), CD28, tumor necrosis factor ligand superfamily member 4 (TNFSF4) and programmed cell death protein 1 (PDCD1) were included in this study to analyze their association with vaccine side effects. Moreover, 61 healthy participants were asked on the number of doses they received, the brand of the vaccine, and the side effects they suffered. We found that several SNPs were associated with side effects after the first or second dose of mRNA or adenoviral vector vaccines. Furthermore, these SNPs were associated with several autoimmune diseases and cancer types; thus, they played an important role in immune regulation. Moreover, rs3181096 and rs3181098 of CD28, rs733618 and rs3087243 of CTLA, and rs1234314 of TNFSF4 were associated with mild vaccine side effects induced by mRNA and adenoviral vector vaccines, which would play a potential role in vaccine-induced immune responses and may further lead to fatal side effects. These results could serve as a basis for investigating the mechanism of vaccine side effects. Furthermore, it was hoped that these results would address public concerns about the side effects of the COVID-19 vaccination. In clinical application, a rapid screening test can be performed to assess the risk of vaccine side effects before vaccination and provide immediate treatment.